2022
DOI: 10.1108/itp-07-2021-0548
|View full text |Cite
|
Sign up to set email alerts
|

Be my friend! Cultivating parasocial relationships with social media influencers: findings from PLS-SEM and fsQCA

Abstract: PurposeThe emergence of social media has brought the influencer marketing landscape to an unprecedented level, where many ordinary people are turning into social media influencers. The study aims to construct and validate a model to yield strategic insights on the relevance of content curation, influencer–fans interaction and parasocial relationships development in fostering favorable endorsement outcomes (i.e. purchase intention).Design/methodology/approachThe present study analyzes data from a survey of 411 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 113 publications
1
34
0
4
Order By: Relevance
“…The literature outlined the importance of a cost–benefit perspective in understanding cryptocurrency adoption. Nonetheless, adopting a disruptive technology, such as cryptocurrency, requires a more comprehensive consideration that encompasses personal and external environmental factors (Aw et al , 2023a; Chuah et al , 2021). Unfortunately, the current literature did not facilitate an adequate understanding of this area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature outlined the importance of a cost–benefit perspective in understanding cryptocurrency adoption. Nonetheless, adopting a disruptive technology, such as cryptocurrency, requires a more comprehensive consideration that encompasses personal and external environmental factors (Aw et al , 2023a; Chuah et al , 2021). Unfortunately, the current literature did not facilitate an adequate understanding of this area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A survey found that social media content attributes of prestige and expertise and interaction strategies of interactivity and self-disclosure had a positive impact on parasocial relationship. Parasocial relationship had a positive impact on purchase intention (Aw et al , 2022). One experimental study showed that if young online influencers on Instagram disclose that their social media feeds are sponsored or contain advertising messages from brands, the level of advertising recognition and brand recall is higher than without clear disclosure (Boerman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory has been widely applied to different consumer behavior contexts, such as retailing (Chang, Eckman, and Yan 2011), e-marketing (Kamboj et al 2018), hospitality marketing (Emir et al 2016), and tourism marketing (Rajaguru 2014). In the past decade, the S-O-R model has been widely used in influencer marketing studies to measure the impact of online influencers as stimuli of affective organisms and subsequent behavioral responses (Aw et al 2023; Gamage and Ashill 2023; Ingrassia et al 2022; Lee and Chen 2021; Lin et al 2022; Seçilmiş, Özdemir, and Kılıç 2022; Zhou et al 2021). In Table 1, we summarize some recent studies using the S-O-R model in online influencer marketing settings to illustrate why we chose to use this model to study influencers’ impact on impulsive behavior in live streaming e-commerce.…”
Section: Theoretical Backgroundmentioning
confidence: 99%